2017
DOI: 10.2139/ssrn.2952510
|View full text |Cite
|
Sign up to set email alerts
|

At Least Bias Is Bipartisan: A Meta-Analytic Comparison of Partisan Bias in Liberals and Conservatives

Abstract: Both liberals and conservatives accuse their political opponents of partisan bias, but is there empirical evidence that one side of the political aisle is indeed more biased than the other? To address this question, we meta-analyzed the results of 51 experimental studies, involving over 18,000 participants, that examined one form of partisan bias --the tendency to evaluate otherwise identical information more favorably when it supports one's political beliefs or allegiances than when it challenges those belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 57 publications
3
81
1
1
Order By: Relevance
“…For example, political homogeneity may lead to premature scientific foreclosure-the erroneous belief that science has settled some question, thereby discouraging further work on the topic that might reveal the error. For example, social psychology prematurely foreclosed on conclusions emphasizing the power of self-fulfilling prophecies (Jussim, 2012), the greater susceptibility to bias among conservatives than liberals (Ditto et al, 2018), the existence of higher levels of prejudice among conservatives than liberals (Brandt, Reyna, Chambers, Crawford, & Wetherell, 2014), and the power and pervasiveness of "unconscious prejudice" (Jussim,8 Careem,Goldberg,Honeycutt,& Stevens,in press). In each case, a 'consensus' in support of the erroneous perspective could be found in the scientific literature that lasted decades.…”
Section: Questions Askedmentioning
confidence: 99%
“…For example, political homogeneity may lead to premature scientific foreclosure-the erroneous belief that science has settled some question, thereby discouraging further work on the topic that might reveal the error. For example, social psychology prematurely foreclosed on conclusions emphasizing the power of self-fulfilling prophecies (Jussim, 2012), the greater susceptibility to bias among conservatives than liberals (Ditto et al, 2018), the existence of higher levels of prejudice among conservatives than liberals (Brandt, Reyna, Chambers, Crawford, & Wetherell, 2014), and the power and pervasiveness of "unconscious prejudice" (Jussim,8 Careem,Goldberg,Honeycutt,& Stevens,in press). In each case, a 'consensus' in support of the erroneous perspective could be found in the scientific literature that lasted decades.…”
Section: Questions Askedmentioning
confidence: 99%
“…For example, perceiving other people to value more benevolence and universalism is positively correlated with various measures of civic engagement such as voting (Sanderson et al , ). Previous research suggested that perception asymmetries exist across the political spectrum (Ditto et al , ). We therefore did not expect significant mean differences for perceived values.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to breeding clear derogation and animosity between groups, the liberal-conservative ideological divide can also lead to political segregation wherein liberals and conservatives actively seek to separate themselves from the other, both physically and psychologically. Moreover, both sides of the divide believe their counterparts to be substantially more biased than they themselves are (Ditto et al, 2017). However, in contrast to these beliefs, a meta-analysis of 41 studies demonstrated that both liberals and conservatives are equally biased in terms of accepting information to confirm their own political beliefs (Ditto et al, 2017).…”
Section: Political Polarizationmentioning
confidence: 99%
“…Moreover, both sides of the divide believe their counterparts to be substantially more biased than they themselves are (Ditto et al, 2017). However, in contrast to these beliefs, a meta-analysis of 41 studies demonstrated that both liberals and conservatives are equally biased in terms of accepting information to confirm their own political beliefs (Ditto et al, 2017). This leads individuals at each side of the political spectrum to choose to live in their own "moral echo chambers," wherein they selectively affiliate with others and expose themselves to information sources that confirm their political values and beliefs, and actively suppress, derogate or ignore opposing arguments.…”
Section: Political Polarizationmentioning
confidence: 99%